Efficient extraction of tungsten, calcium, and phosphorus from low-grade scheelite concentrate. (15th May 2022) - Li, Jiangtao; Yang, Jinhong; Zhao, Zhongwei; Chen, Xingyu; Liu, Xuheng; He, Lihua; Sun, Fenglong
Graphical abstract: Highlights: Scheelite and apatite in low-grade scheelite were digested completely by HNO3 . Tungsten was leached in the form of soluble phosphotungstic acid. Calcium was leached and recovered in the form of gypsum whiskers. The excess phosphorus can be recovered in the form of nitrophosphate fertilizer. Abstract: In the traditional process for tungsten recovery from scheelite concentrate, phosphorus is regarded as a harmful impurity that should be strictly controlled. Moreover, the calcium that entered the resideue as Ca(OH)2 or CaCO3 was discarded or landfilled. To date, the residues from the traditional process have been listed as solid hazardous waste in China. A novel method was investigated to realize the comprehensive recovery of tungsten, phosphorus, and calcium. In the leaching process, 96% of scheelite (CaWO4 ) and 99% of apatite (Ca5 (PO4 )3 F) were digested under the conditions of 3 M HNO3, at a liquid/solid ratio of 10:1, a leaching temperature of 90 °C, and leaching time of 2 h. After extracting tungsten from the leaching solution by solvent extraction, about 70% of Ca 2+ in the raffinate was recovered as calcium sulfate whiskers by adding H2 SO4 . Subsequently, the solution from the calcium removal process was reused to leach scheelite after adding the consumed HNO3 . When the P2 O5 concentration in the circulating leaching solution was over 30%, it was discharged and neutralized by NH3 ·H2 O, and then used to produce a nitrophosphate fertilizer by spray granulation and drying processes.